MEMBANGUN SISTEM SUMBER DAYA MANUSIA BERBASIS KOMPETENSI DAN PROFESIONAL - Sulistyaningsih, Elli (Universitas Persada Indonesia YAI, 2018)
The role of human resources that is affirmed in the outlines of the State Policy that the essence ofIndonesias national development is to build a complete Indonesian people and the entire Indonesian people. Inaddition, in the General Pattern of Long Term Development II it is also emphasized that the main objective ofnational development is to improve the quality of people and the people of Indonesia. Human resources is thedriving force of the activities of a country, where the citizens of the country concerned that run all the activitiesof the state, such as politics, economy and others. In addition to running the wheels of government, residentsalso manage all natural resources that become wealth for the country concerned. The population of a goodquality country will strive to cultivate and utilize existing natural resources, to meet the needs of life andimprove their welfare and to manage their countrys wealth properly and efficiently. Development ofcompetency-based and professional-based human resources is conducted in order to deliver results inaccordance with organizational goals and objectives with predefined performance standards. Professionalhuman resources are those who have the competence, in accordance with the profession that ditekuni. Theobjective to be achieved by human resource management is to form professional human resources, which havecharacteristics, noble, competent, and motivated.